Edible vegetable oils: changing demands and opportunities - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1994)
Several vegetable oils are used widely in human and animal nutrition and in industry. Scientifically they are known as lipids: oils when liquid, fats when solid. They are derived from a variety of annual and biennial crops (soya, sunflower,...